2018
DOI: 10.1002/pi.5668
|View full text |Cite
|
Sign up to set email alerts
|

Conductive films of sonicated multiwall carbon nanotubes on stretchable substrates

Abstract: Conductive films were prepared on stretchable substrates by mixing sonicated multiwall carbon nanotubes (MWCNTs) with room‐temperature‐vulcanized silicone rubber. Microscopic investigations show a broad range of MWCNT particles with diameters in the range 15–17 nm, lengths from a few nanometers to a few micrometers, and thus a high aspect ratio of 55–70. The sonicated MWCNTs have 40 wrapped graphene layers and an out‐of‐plane correlation length of 13 nm. Also, the grain size of the dispersed sonicated MWCNTs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…[9,10] At low filler content, the CNT reinforced polymeric materials have higher actuation and energy harvesting properties. [11][12][13] Efficient interfacial bonding between the polymer and the nanomaterial causes the smooth load transfer. [14] High stiffness, high strength to weight ratio, and very low density of CNT made it as the superior material for various industrial applications with excellent physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] At low filler content, the CNT reinforced polymeric materials have higher actuation and energy harvesting properties. [11][12][13] Efficient interfacial bonding between the polymer and the nanomaterial causes the smooth load transfer. [14] High stiffness, high strength to weight ratio, and very low density of CNT made it as the superior material for various industrial applications with excellent physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its simple processing, low viscosity, high tensile strength, ideal curing, and reinforcing qualities, silicone rubber is frequently employed [45]. The widespread usage of silicone rubber in many industrial applications, including actuators and sensors, is just one of its many benefits [46][47]. Numerous studies have demonstrated that silicone rubber reinforced with MWCNTs nanofillers has improved mechanical strength, electrical characteristics, filler dispersion, and compatibility with silicone rubber in industrial applications like actuators [48].…”
Section: Introductionmentioning
confidence: 99%
“…A special class of nanogenerators namely piezoelectric nanogenerators (PENG) and triboelectric nanogenerators have been used to harvest these waste energies. [10][11][12][13][14][15] These devices are biocompatible and have a superior life span. [16][17][18][19][20] Several studies have been conducted on various energy-harvestingdevices-based sensor technologies such as self-powered force sensors, surveillance systems, and health-monitoring systems, which employ piezoelectric materials.…”
Section: Introductionmentioning
confidence: 99%